2000
DOI: 10.1086/309387
|View full text |Cite
|
Sign up to set email alerts
|

Rossby‐Type Wave–Induced Periodicities in Flare Activities and Sunspot Areas or Groups during Solar Maxima

Abstract: The Gamma-Ray Spectrometer (GRS) aboard the Solar Maximum Mission (SMM) discovered a 154 day periodicity in solar Ñare rates. Subsequently, periodicities in various solar Ñare activities and in sunspot areas or groups during a few years around solar maxima have been extensively monitored using di †erent diagnostics and at many electromagnetic wavelengths. Notable periods are D154, 128, 102, 78, and 51 days during maxima of di †erent solar cycles from various data sets. The origin of such quasi periodicities pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
134
0
16

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(161 citation statements)
references
References 51 publications
(65 reference statements)
11
134
0
16
Order By: Relevance
“…Recently, Lou (2000) has shown that for typical solar parameters, equatorially trapped Rossby waves with n \ 1(2) and m \ 13 have periods around 164 days, while for equatorially trapped mixed waves with n \ 0 and m \ 12, the Rossby-Poincare obtained period is around 151 days, both in good agreement with the period of the above reported periodicity. Also, Lou (2000) suggests that Rossby-type waves could lead to magnetic Ñux eruption through the modulation of the onset of magnetic buoyancy instabilities, leading to the appearance of Ñares in active regions. However, in spite of this plausible scenario, several important points still remain to be explained, for instance : Why does this periodic emergence of magnetic Ñux take place in already formed active regions setting up a complex magnetic conÐguration ideally suited for the occurrence of high-energy Ñares ?…”
Section: Results and Conclusionsupporting
confidence: 79%
See 2 more Smart Citations
“…Recently, Lou (2000) has shown that for typical solar parameters, equatorially trapped Rossby waves with n \ 1(2) and m \ 13 have periods around 164 days, while for equatorially trapped mixed waves with n \ 0 and m \ 12, the Rossby-Poincare obtained period is around 151 days, both in good agreement with the period of the above reported periodicity. Also, Lou (2000) suggests that Rossby-type waves could lead to magnetic Ñux eruption through the modulation of the onset of magnetic buoyancy instabilities, leading to the appearance of Ñares in active regions. However, in spite of this plausible scenario, several important points still remain to be explained, for instance : Why does this periodic emergence of magnetic Ñux take place in already formed active regions setting up a complex magnetic conÐguration ideally suited for the occurrence of high-energy Ñares ?…”
Section: Results and Conclusionsupporting
confidence: 79%
“…Later, Bai & Sturrock (1993) modiÐed the earlier period to the value 25.50 days, but that model seems to be very constrained by helioseismological data about the rotation of the SunÏs interior. Recently, Lou (2000) has suggested that such periodicities can be related to large-scale equatorially trapped Rossbytype waves showing that, for typical solar parameters, the periods of these waves are in good agreement with the observed ones. Moreover, Lou has also pointed out that such waves can give rise to detectable features, such as surface elevations in the photosphere.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Since the rotation period of CoRoT-2 is only 4.5 days, this would correspond to a wave period of ∼27 days, close to the periodicity of 28.9 days found by Lanza et al (2009) from the modelling of the out-of-transit light modulation. Moreover, other periodicities, ranging from 2 to 6 rotation periods, have been reported from the analysis of different solar data sets (Lou 2000). In the case of CoRoT-2, we found in Sect.…”
Section: Resultssupporting
confidence: 67%
“…The periodicity of the spotted area variations is close to 4 times the mean rotation period of the star, while in the Sun it is ≈6 times and in CoRoT-2 is ≈6.5 times the rotation period. Those oscillations of the spotted area may be associated with hydromagnetic Rossby-type waves propagating in the upper part of the convection zone or at the interface between the radiative interior and the convection zone where the dynamo is probably located (Lou 2000;Zaqarashvili et al 2010). Since only a few examples of stars displaying Rieger-type cycles are known (cf., Massi et al 2005;Lanza et al 2009a), the new results on Kepler-17 are particularly interesting for a better understanding of this phenomenon in the framework of the solar-stellar connection.…”
Section: Resultsmentioning
confidence: 99%